Strategi Guru Pendidikan Agama Islam dalam Mengatasi Kesulitan Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di SDN 15 Ampang Gadang - Astuty Hariati Hasibuan; Charles Charles; Supratman Zakir; Pendi Hasibuan (Reflection : Islamic Education Journal, 2025)
The Strategy of Islamic Religious Education Teachers in Overcoming Student Learning Difficulties in Islamic Religious Education Subjects at SDN 15 Ampang Gadang, namely providing opportunities for students to develop their potentials or abilities optimally, and students' thinking power is actively stimulated which makes students Be diligent. By using this strategy, students are more active and often repeat their learning materials. Second, change the teaching method with a method that suits the student's ability, namely using a project-based method that makes students more active and pay more attention to the lesson. Three, giving special attention to students with Learning Disorder (learning disorder) so as to foster a sense of love, affection, and provide attention savings that can be applied to students with Learning.